Efficacy of dry cupping therapy on nonspecific chronic low back pain: Systematic literature review with meta-analysis: Effectiveness of cupping therapy on low back pain - Beatriz Pinheiro, Lauanne; F. Gonçalves, Sabrina; H. Campos, Mário (Manual Therapy, Posturology & Rehabilitation Journal, 2025)
Background: Nonspecific chronic low back pain (NCLBP) is a painful symptom in the lower spine that lasts for more than 3 months and does not have any apparent harmful involvement. Cupping therapy is an Chinese instrumental technique that has been used in musculoskeletal conditions. It consists of applying suction cups to the skin, causing vasodilation of blood capillaries, production of endogenous opioids, and increased microcirculation that appear to block nerve pain impulses. Objectives: to find evidence in the literature of the use and efficacy of cupping therapy as a treatment for NCLBP. Methods: Systematic review with meta-analysis, performed by two independent researchers. A search for randomized controlled clinical trials was performed in the Pubmed, PEDro, Science Direct, and LILACS databases that included the use of dry cupping therapy in cLBP. There was no restriction on sex, language, or year of publication. RevMan software was used for the meta-analysis. Results: Of the 91 articles initially found, after applying all criteria, 3 studies were used in this review. The studies performed interventions of 5 sessions, 3 and 8 weeks, observing immediate and late post-operative results. Two studies had placebo cupping therapy (Sham) as a control and another, a control that did not undergo any intervention. The points worked were the meridians of BL23, BL24, BL25, BL26, GV4, BL30, BL40, BL58. Cupping therapy was superior to placebo therapy in only one article, however, when compared with another intervention (hot pack) there was no significant difference. The meta-analysis did not indicate superiority between the experimental and control groups. Conclusion: Dry cupping therapy proved to be a safe therapy, however without superior results to another therapy or placebo. In addition, more Randomized Controlled Trials (RCTs) are needed, since there were few studies investigating the use of cupping therapy in cLBP with adequate methodology.